Influencia de la participación de los actores educativos en la gestión de cambio institucional en las instituciones educativas secundarias urbanas del distrito de Iquitos 2019 - Gómez Sánchez, Jorge Luis (2022)
The purpose of this research was to explain the influence of stakeholders’ participation in institutional change management of urban secondary schools at Iquitos district, 2019. The type of study was explanatory with field study, contemporary and multivariate designs. The population consisted of 869 teachers, 13,315 students, 8,311 parents, and a stratified sample with proportional allocation of 267 teachers, 373 students and 367 parents. Data gathering technique was a survey and a validated questionnaire (with a Cronbach's Alpha coefficient of 98% reliability). Results showed that 58.97% of respondents consider that the educational actors’ participation at the informative level is good. However, in its other dimensions their participation is deficient: 57.32% at advisory level. 50.73% at propositional level and 89.04% at resolution level. In conclusion, the stakeholders’ participation variable at the informative, advisory, and propositional levels has a significant influence on the institutional change management variable (p-value < ?=0.05) and the stakeholder´s participation variable at the resolution level is not statistically significant on the institutional change management variable (p-valor=0,995>0,05). The model presents a coefficient of determination of 35.6% to 49.3% with 76.8% accuracy.